CONTRASTIVE PHONOLOGICAL FEATURES OF SINGLISH ON SELECTED YOUTUBE VIDEOS - Siti Radibah Imatufariq; Evynurul Laily Zen; Harits Masduqi; Masrokhin Masrokhin (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
The present study is intended to investigate the contrasting phonological features of Singlish with the specific aim of finding out how the pronunciation of vowels in Singlish differs from Standard English and the potential factors influencing the Singlish vowel pronunciation. Five YouTube videos containing 19 targeted words uttered by three Singlish speakers became the data source. The auditory analysis method was used to find distinctive vowels between Singlish and Standard English. The descriptive qualitative method was then used to determine the factors influencing the Singlish phonological differences. The results show that Singlish speakers tended to change the /ə/ to /ɜː/, not be able to distinguish the /ə/ and /e/ and have no rules in long and short vowel systems. All these differences are likely a result of contact language situations in Singapore that has been in place for years.